The triage process in rehabilitation centers - Riberto, Marcelo; Jucá, Sueli Satie Hamada; Miyazaki, Margarida Harumi; Battistella, Linamara Rizzo (Acta Fisiátrica, 2010)
The triage process in rehabilitation centers consists of an evaluation of the conditions of a patient who might use the services of these units in the health system. In general it takes place at first contact with the clinical team. By schedule a patient is interviewed by a doctor, a social worker, and a psychologist at the same time whereby they verify the clinical conditions, relationship dynamics and psychopathological aspects, as well as the social requirements for regular supervised participation in the prescribed activities. The object of the triage process is not to obstruct access of anyone to the services available, but to guide the potential user either to the easiest form of treatment or to that most appropriate to his needs. At the end of the triage process the patient may be chosen for multi-professional intervention several days a week or other alternative interventions, either therapeutic or guiding, with the recruitment of any number of professionals or weekly contacts. Considering the reality of rehabilitation in Brazil, which does not include internment, one can expect full service of the rehabilitation program only under optimal conditions. Resources for rehabilitation are limited, therefore its optimization is necessary, and the triage process enables the best use of these resources with a fair and ethical distribution.